Pembuatan Peta 3D Urban Model Untuk Visualisasi Dampak Banjir - Adkha Yulianandha Mabrur; Feny Arafah; Fransisca Dwi Agustina; Lalu Teguh Suganda (LPPM, 2022)
3D modeling is a process to create 3D objects that you want to put in a visual form. A 3D model is a mathematical representation of any three-dimensional object (either inanimate or living). A model is technically graphical until it is visually displayed. Because 3D models are not limited to virtual space. A model can be displayed visually as a two-dimensional image through a process called 3D rendering, or used in non-graphical computer simulations and calculations. In this case, the geographic information system can present a form of modeling of a hydrological phenomenon such as flooding in an area. This study aims to analyze the flood and visualize it in the form of three-dimensional modeling to see the impact of a flood threat due to the Jelateng river’s overflow. This study emphasizes information related to the impact caused by the overflow of the Jelateng river. Making a 3D urban map model will be used as a representation of the appearance of the Jelateng river area and then it will be visualized using DEMNAS data on the arcscene with the animation manager so that the visualization can be seen according to the scenario that will be carried out. The results of the research will be published in a journal so that it can be a reference for some users who want to know related information from the research results